2020
DOI: 10.3390/v12111336
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performances of Different Genome Amplification Assays for the Detection of Swine Vesicular Disease Virus in Relation to Genomic Lineages That Circulated in Italy

Abstract: During the last 25 years, swine vesicular disease (SVD) has occurred in Italy mostly sub-clinically. Therefore, regular testing of fecal samples from suspected holdings and high turnover premises was fundamental to identifying virus circulation and to achieve SVD eradication. In this study, we evaluated diagnostic performances of six genomic amplification methods, using positive fecal samples from 78 different outbreaks (1997–2014), which included different lineages. Comparison of three RT-PCRs, designed to am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Thus, 28948C >T is the sole mutation characterizing the N-negative B.1.177.75 samples with respect to N-positive strains belonging to the same lineage. It is known that few mismatches in the oligonucleotide binding region can affect the amplification efficiency, with prevention of any amplification when located in the very 3' end of the primer(s) or on the middle of the TaqMan probe (25)(26)(27). In a TaqMan assay for detection of rabies virus RNA, the number of sequence mismatches between gene-specific oligonucleotides and the target sequence significantly affected amplification and point mutations at the center of the probe resulted in false-negative results through the prevention of probe binding and subsequent fluorescence (28).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 28948C >T is the sole mutation characterizing the N-negative B.1.177.75 samples with respect to N-positive strains belonging to the same lineage. It is known that few mismatches in the oligonucleotide binding region can affect the amplification efficiency, with prevention of any amplification when located in the very 3' end of the primer(s) or on the middle of the TaqMan probe (25)(26)(27). In a TaqMan assay for detection of rabies virus RNA, the number of sequence mismatches between gene-specific oligonucleotides and the target sequence significantly affected amplification and point mutations at the center of the probe resulted in false-negative results through the prevention of probe binding and subsequent fluorescence (28).…”
Section: Discussionmentioning
confidence: 99%
“…Pigs infected with SVDV can shed large amounts of the virus through the nose, mouth and feces to contaminate the surrounding environment. Given the absence of clinical signs, feces are the sample of choice for viral testing to identify subclinical infections ( Pezzoni et al, 2020 ). Sensitive detection methods are necessary due to the low viral content of stool samples.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Sensitive detection methods are necessary due to the low viral content of stool samples. The diagnostic performance of six genomic amplification methods for SVDV detection including RT-PCR, real-time RT-PCR and RT-LAMP assay was evaluated and the result showed that the conventional 3D RT-PCR and the 3D rtRT-PCR using SYBR Green as a detector were still the most sensitive and efficient methods for detecting SVDV in fecal samples ( Pezzoni et al, 2020 ). However, compared with RT-qPCR, the procedure of RT-PCR is more complicated, and agarose gel electrophoresis is required to determine the results of the corresponding samples.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Consensus sequences were aligned using MAFFT 7.475 [ 12 ]. All of the strains were characterised as belonging to sub-lineage 1 of the fourth SVDV antigenic/genomic variant; this sub-lineage comprises of viruses that evolved in Italy after its original introduction in 1992 [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Italy, the fourth SVDV antigenic variant [ 5 ] has been circulating for more than 20 years, mainly in Italy’s southern regions with sporadic incursions in the north of the country. During the last 20-year period, two different lineages have been detected in Italy: one evolved exclusively in Italy from viruses first introduced in 1992, and the second one was detected in2004 and is closely related to the viruses circulating in Portugal during 2003, 2004, and 2007 [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%